2004
DOI: 10.1038/sj.gt.3302338
|View full text |Cite
|
Sign up to set email alerts
|

Brain transplantation of genetically modified bone marrow stromal cells corrects CNS pathology and cognitive function in MPS VII mice

Abstract: Current therapies for lysosomal storage diseases (LSDs), enzyme replacement therapy and bone marrow transplantation are effective for visceral organ pathology of LSD, but their effectiveness for brain involvement in LSDs is still a subject of controversy. As an alternative approach, we transplanted genetically modified bone marrow stromal (BMS) cells to lateral ventricle of newborn mucopolysaccharidosis VII (MPS VII) mice. MPS VII is one of LSDs and caused by deficiency of beta-glucuronidase (GUSB), resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…In fact, transplantation of b-glucuronidase-expressing neural progenitor cells into the brain of mucopolysaccharidosis mice led to a reduction and in the case of transplantation of b-glucuronidase overexpressing bone marrow stromal cells to an almost complete normalization of glycosaminoglycan storage in the treated animals. 22,33 These diverse results indicate that the therapeutic efficacy of cell-based enzyme delivery cannot be generalized for all lysosomal storage disorders but depends critically on disease-specific parameters such as secretion rates, diffusion distance and interaction with the storage compound.…”
Section: Different Lysosomal Storage Diseases May Exhibit Different Amentioning
confidence: 99%
“…In fact, transplantation of b-glucuronidase-expressing neural progenitor cells into the brain of mucopolysaccharidosis mice led to a reduction and in the case of transplantation of b-glucuronidase overexpressing bone marrow stromal cells to an almost complete normalization of glycosaminoglycan storage in the treated animals. 22,33 These diverse results indicate that the therapeutic efficacy of cell-based enzyme delivery cannot be generalized for all lysosomal storage disorders but depends critically on disease-specific parameters such as secretion rates, diffusion distance and interaction with the storage compound.…”
Section: Different Lysosomal Storage Diseases May Exhibit Different Amentioning
confidence: 99%
“…Progress along those lines has been made in rodent models of neurodegenerative disorders, such as Parkinson's disease [13,60], and lysosomal storage disorders, including Tay-Sachs disease [53], Niemann-Pick disease types A and B [61,62], and mucopolysaccharidosis Type VII [63].…”
Section: Mesenchymal Stem Cells As Platforms For Recombinant Protein mentioning
confidence: 99%
“…Various cell sources have been tested either alone as intracranial injections [Snyder et al 1992, Buchet et al 2002, Meng et al 2003, Newman et al 2004, Sakurai et al 2004, or as adjunct therapies to HSCT [Jin et al 2003]. Although human mesenchymal stem cells (MSCs) produce several lysosomal enzymes [Koc et al 1999] no other presently identified source of neural stem cells produces enough endogenous lysosomal enzymes, and must overexpress the proteins from an integrating vector to provide a cross corrective function [Lacorazza et al 1996, Buchet et al 2002, Meng et al 2003, Shihabuddin et al 2004, Sakurai et al 2004].…”
Section: Neural and Mesenchymal Stem Cellsmentioning
confidence: 99%